2013
DOI: 10.4322/rbeb.2013.039
|View full text |Cite
|
Sign up to set email alerts
|

Implantes cocleares: aspectos tecnológicos e papel socioeconômico

Abstract: Resumo Introdução: O grande número de defi cientes auditivos faz da perda auditiva um sério problema social, econômico e de saúde pública. Próteses auditivas e implantes cocleares representam os principais dispositivos utilizados como paliativos por pessoas com defi ciência auditiva, sendo que os implantes cocleares são muitas vezes a única opção nos casos de defi ciência auditiva severa e profunda. Nesse artigo discute-se de maneira geral os diferentes aspectos envolvendo implantes cocleares, tanto de âmbito … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 90 publications
0
3
0
3
Order By: Relevance
“…In Brazil, the number of deaf children who have undergone cochlear implant surgery (CI) is increasing in order to acquire hearing close to normal thresholds and thus develop oral language (1)(2)(3) . This requires hearing habilitation and rehabilitation through rehabilitators to help these children and their families through the language acquisition stages (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the number of deaf children who have undergone cochlear implant surgery (CI) is increasing in order to acquire hearing close to normal thresholds and thus develop oral language (1)(2)(3) . This requires hearing habilitation and rehabilitation through rehabilitators to help these children and their families through the language acquisition stages (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…One key aspect that imposes limitations to their use is the presence of a external elements, which houses the microphones, signal processor, battery and, in the case of MEIs and CIs, the RF antenna. Besides the cosmetic aspect, patients relate that the existence of external parts of the device imposes drawbacks such as: vulnerability of the device, the possibility of detachment , to break and to be lost or stolen [ 1 , 3 ]. Further on, most devices cannot be used under water, during intense physical activities or even while the user is asleep.…”
Section: Introductionmentioning
confidence: 99%
“…The process of hearing loss due to the death of hair cells in the cochlea is directly linked to the process of aging, and there are reasons to suspect that CI in elderly adults may have limited results because of the degeneration of spiral ganglion cells and neural pathways leading to the cortex. Studies using neuroimaging have found an association between hearing loss and atrophy of the cerebral and temporal cortex that may result from a combination of interdependent mechanisms, for example, vascular risk factors, neurodegenerative processes affecting the peripheral auditory pathways and the cerebral cortex, social isolation, and lack of cognitive stimulation.…”
mentioning
confidence: 99%